2020
DOI: 10.3390/coatings10060539
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer-Deposited Al-Doped ZnO Thin Films for Display Applications

Abstract: The integration of high uniformity, conformal and compact transparent conductive layers into next generation indium tin oxide (ITO)-free optoelectronics, including wearable and bendable structures, is a huge challenge. In this study, we demonstrate the transparent and conductive functionality of aluminum-doped zinc oxide (AZO) thin films deposited on glass as well as on polyethylene terephthalate (PET) flexible substrates by using an atomic layer deposition (ALD) technique. AZO thin films possess high optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…To sum up, the optimal AZO films exhibit a low resistivity of about 1 Ω·cm and a high transmittance above 75%, which are comparable to previous works [ 19 , 22 , 25 ]. Thus, the ALD-deposited AZO films in this work have a great potential to be used as transparent electrodes.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To sum up, the optimal AZO films exhibit a low resistivity of about 1 Ω·cm and a high transmittance above 75%, which are comparable to previous works [ 19 , 22 , 25 ]. Thus, the ALD-deposited AZO films in this work have a great potential to be used as transparent electrodes.…”
Section: Resultssupporting
confidence: 88%
“…Recently, the ALD process has been of increasing interest in the fabrication of AZO films. Dimitrov et al [ 19 ], Marques et al [ 20 ], and Li et al [ 21 ] studied ALD-deposited flexible AZO films with high transmittance and low resistance. Swatowska et al [ 22 ], Li et al [ 23 ], and Wu et al [ 24 ] investigated Al concentration on the properties of ALD-deposited AZO films.…”
Section: Introductionmentioning
confidence: 99%
“…The time required for transmittance to change from T 10% to T 90% is the response time. The obtained response time and the decay time values of ~78 ms and ~74 ms, respectively are in good agreement with those reported for PDLC-based devices using other transparent contacts [ 37 , 38 , 39 ].…”
Section: Resultssupporting
confidence: 89%
“…The nonlinear two-photon absorption coefficient of titanium dioxide was determined by means of the laser-induced deflection technique at a wavelength of 800 nm. Dimitrov et al [3] demonstrated transparent and conductive aluminum-doped zinc oxide (AZO) thin films deposited on rigid and transparent substrates through atomic layer deposition. Applications as transparent conductive layers in AZO/glass-supported liquid crystal displays and flexible polymer-dispersed liquid crystal devices were discussed.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%